Constructivist Self-Construal: A Cross-Cultural Comparison. (February 2022) - Ge, Fiona; Syropoulos, Stylianos; Gensler, Julian; Leidner, Bernhard; Loughnan, Steve; Chang, Jen-Ho; Harada, Chika; Mari, Silvia; Paladino, Maria P.; Shi, Junqi; Yeung, Victoria W. L.; Kuo, Chun-Yu; et al.
Building on independent versus interdependent self-construal theory, three studies provide initial empirical evidence for a third way of construing the self: the constructivist self-construal. People with a constructivist view perceive the self as constantly changing (impermanence), as a collection of distinct phenomena from moment to moment (discontinuity), as lacking an essence (disentification), and as psychologically overlapping with other people and things in the universe (boundlessness/boundaries). In Study 1, we piloted a new Constructivist Self-Construal Scale and established preliminary evidence for the discriminant validity of the scale. Studies 2 and 3 found that across seven countries with diverse cultural backgrounds, the self was consistently cognitively represented on the four dimensions of constructivist self. People from collectivistic cultures where Buddhist philosophy is more prevalent tended to endorse the dimensions of the constructivist self-construal to a greater degree than people from other cultures. Implications regarding the development of the constructivist self-construal and future research recommendations are discussed.